'It's not something that I should be ashamed of' understanding the challenges and lived experiences of disadvantaged students during the Covid-19 pandemic. Issue 3 (7th November 2022) - Thiele, Tamara; Homer, Damien
The pervasive socioeconomic inequalities that exist in relation to higher education participation within the UK are notably prominent amongst the most selective, 'elite' universities, and could become wider still following the Covid-19 pandemic. This case study privileges the accounts of 11 young people from low socio-economic status (SES) backgrounds who were directly affected by the pandemic during their final year at school (Year 13) and who had all taken in part in outreach programmes that specifically aimed to improve access to such top universities in England. Through in-depth phenomenological interviews, this provides insight into the educational and life journeys of these individuals, including their experiences of the pandemic and their interactions with outreach programmes, helping to understand the influence they perceived these to have on their choices, aspirations and trajectories. Findings highlight barriers and challenges that could influence the demand for higher education, some which were amplified by the pandemic. These included issues related to individuals' personal/home circumstances, finance, the schools they attended, but also issues associated with fit and belonging that have been shown to deter many low SES students from applying to top universities.